Análise da constitucionalidade da imposição do regime da separação obrigatória de bens aos maiores de 70 anos de idade - Nery, Juliana Simioni (2024)
The objective of the research carried out was to verify to what extent the imposition of the mandatory separation of assets regime for those over 70 years of age by article 1,641, II, of the Civil Code violates the Federal Constitution of 1988. An initial analysis of the institute was carried out of marriage and stable unions, their main aspects and requirements, as well as the applicable principles. In its patrimonial aspect, the existing property regimes and the peculiarities of each one, where research later focused on the mandatory separation regime, legally imposed for those over 70 years of age. Based on this, the position of the doctrine was used, that is, a bibliographical and jurisprudential research, and the deductive method was used. Coming to the conclusion of the possibility of changing this article of law, I consider the possibility of declaring article 1,641, II, of the Civil Code unconstitutional.